How Flexible are Wages in EU Accession Countries? - Anna Iara; Iulia Traistaru (European Regional Science Association (ERSA), 2004)
The transition to a market economy and increased economic integration have fostered regional disparities in Central and Eastern European countries. This paper investigates whether and to what extent wages could act as an equilibrating mechanism in these countries by adjusting to local market conditions. Using regional data for the 1990s, we estimate static and dynamic wage curve models for Bulgaria, Hungary, Poland and Romania. We find empirical evidence for a wage curve in Bulgaria, Hungary and Poland suggesting that wages could help equilibrate labour markets following labour demand shocks. In the case of Romania, the unemployment elasticity of pay is not significantly different from zero.
Keywords: 330